Analysis of Turkey’s Institutional Open Repositories: An Example of Dokuz Eylül University Institutional Open Repository - Korhan Levent Ertürk; Gökhan Şengül (Türk Kütüphaneciliği)
After the declaration of the Budapest Open Access Initiative in 2001, institutional open repositories are known as the most important tool of the self archiving, which is also known as green road. There are 26 institutional repositories, which are all compatible to international standards. All the institutional open repositories of Turkey mentioned before are listed in international open archive directories. In this study institutional open repository of Dokuz Eylül University is examined and institutional open repositories of Turkey are discussed.